Seeking the koko' ta'ay : Investigating the Origins of Little People Myths in Taiwan and Beyond - Karalekas, Dean,; Openshaw, Tobie, (Asian Studies E-Books Online, Collection 2024., 2025)
This volume, edited by Tobie Openshaw and Dean Karalekas, will guide you on a multidisciplinary journey through Indigenous peoples' centuries-old lore of "little people" in Taiwan and the Pacific. Learn about the Taiwan SaiSiyat people's paSta'ay ritual , still held to this day to commemorate the koko ta'ay . Follow the distribution of the legends, interspersed with original stories by modern Indigenous authors. Explore the archaeological find of small-statured negrito remains in Taiwan, and delve into the most current research on the topic by linguists, anthropologists, folklorists, and other specialists to unravel the mystery of what-or who-inspired these ancient legends.